The death of the American trial - Burns, Robert P., 1947- (University of Chicago Press, 2009)
In The Death of the American Trial, distinguished legal scholar Robert P. Burns makes an impassioned case for reversing the rapid decline of the trial before we lose one of our public culture's greatest achievements. As a practice that is adapted for modern times yet rooted in ancient wisdom, the trial is uniquely suited to balance the tensions-between idealism and realism, experts and citizens, contextual judgment and reliance on rules-that define American culture. Arguing that many observers make a grave mistake by taking a complacent or even positive view of the trial's demise, Burns conclu.